Design and Implementation of Auto Calibration PV Analyzer Using Arduino UNO and Driver IRFZ440 - Selman, Nasir (Asian Journal of Computing and Engineering Technology, 2025)
Purpose: This research proposes to design a low-cost solar cell performance analyzer that measures voltage, current, and power. The device uses an IRFZ440 MOSFET driver and is controlled by an Arduino UNO board. The system focuses on precise control and straightforward design. The project aims to enhance the understanding of solar panel efficiency in various environments and under different load conditions. With the potential to be developed to support Internet of Things (IoT) technologies and Maximum Power Point Tracking (MPPT) algorithms, the research also seeks to provide a useful and effective tool for monitoring the performance of small-scale solar systems in academic and field settings. Methodology: Methodology: An electronic circuit was designed, consisting of an Arduino UNO microcontroller to read voltage and current sensor signals. An IRFZ440 MOSFET transistor is used as an electronic switch to control the load via a pulse-width modulation (PWM) signal. The load (small electric motor) was connected in series to the solar panel. The measurement results were displayed using a small OLED display. The Arduino was programmed to generate PWM signals at various percentages (from 0% to 100%) to simulate changes in the load on the solar cell. Data was collected under natural light using an 8 W solar cell. The resulting data were analyzed to verify the system's performance and compare its results with the expected theoretical values. Findings: After using the designed system to analyze the performance of solar panels based on the Arduino UNO microcontroller and the IRFZ440 MOSFET driver, positive results were achieved in terms of measurement accuracy and performance efficiency. When applying different PWM signal ratios, a clear change in the voltage, current, and power output of the solar cell was recorded, which enables analysis of the relationship between these variables under different load conditions. The designed circuit was demonstrated to be able to automatically change the load using PWM technology, allowing the panel's response to be monitored under varying load conditions without the need for multiple physical resistors. All readings were displayed in real time on an OLED display. The proposed design proved effective in providing a low-cost, accurate, and scalable solution for future use by integrating it with MPPT or IoT technologies. Unique Contribution to Theory, Practice, and Policy: Presenting a practical, low-cost device that can be used to monitor and analyze solar cell performance in real time. It demonstrates how to use PWM signals to automatically change the load based on the Arduino microcontroller and the IRFZ440 MOSFET driver. Future expansion potential to integrate IoT technologies and MPPT applications. Supporting sustainable and decentralized energy policies by providing simple tools that can monitor small-scale solar systems (such as homes or villages), thus reducing reliance on centralized electricity grids. Potential for use in government or non-profit initiatives seeking to disseminate clean and smart energy solutions in rural communities.